Methods of inoculation of potato tubers when assessing resistance to Phoma exigua - Andriychuk, T.O.; Skoreiko, A.M.; Nemchenko, O.M.; Melnik, A.T. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The results of studies on methods of inoculation of potato tubers when assessing resistance to Phoma exigua. For this is suitable both ways tuber infection, making inokulumu (agar blocks) in the hole and sinking bubbles in the suspension of mycelium fungus.